TRANSFORMING EDUCATIONAL CHANGES IN THE DIGITAL AGE TO FOSTER MORE ENGAGING LEARNING EXPERIENCES - Maba, Wayan; Mantra, Ida Bagus Nyoman; Widiastuti, Ida Ayu Made Sri (As-Sulthan Journal of Education, 2025)
The advancement of information and communication technology has profoundly altered educational models. The engagement between teachers and learners is no longer limited to traditional classrooms but expands to various online platforms. A qualitative method utilizing a descriptive-analytical approach has been implemented in this study. Information was gathered through detailed interviews with teachers, observations within academic environments, and reviews of existing literature. The analysis reveals trends in how teachers are adapting to technological advancements. The findings indicate that digitalization has redefined the role of teachers as the leading providers of knowledge, reducing their authority from students' perspective. While technology enhances accessibility to learning resources, it also brings ethical challenges, including a rise in consumer-oriented attitudes and a preference for instant gratification. Teachers must effectively integrate technology into their teaching, devise innovative strategies, and reconcile technological progress with character education to stay relevant. Therefore, transformations in education can serve as opportunities to enrich the overall quality of learning.